DIFFERENCES IN THE HINDLIMB ANATOMY IN THE TWO SPECIES OF THE LATE TRIASSIC DREPANOSAUROMORPH DIAPSID MEGALANCOSAURUS INDICATE HABITAT PARTITIONING WITHIN THE ARBOREAL ENVIRONMENT (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Discovery of two different morphologies of the hindlimb in specimens ascribed to the Triassic drepanosauromorph diapsid Megalancosaurus led to the erection of two distinct species within this genus: M. preonensis and M. endennae. In the present study a re-examination of the hindlimb architecture of both Megalancosaurus species indicates that M. preonensis and M. endennae exploited different microhabitats within the arboreal environment as for many extant species belonging to the same genus, like caribbean Anoles. M. endennae, with a stronger lower leg, a larger grasping foot, an opposable clawless hallux, and deeper and more recurved claws on pedal digits 2-5 was better adapted for locomotion on narrow and intricate supports like narrow twigs on terminal branches. M.preonensis with more slender hindlimbs, absence of an opposable hallux and longer, but thinner and less recurved claws on all pedal digits may have been better adapted to live on larger supports and could also have used the long pedal claws as hooks in a sloth-like fashion. In both Megalancosaurus species the tail acted both as a prop to assume a stable tripodal gait and as a clinging device that ensured grip during bridging as in other arboreal drepanosauromorphs which skeleton is adequately known. The overall hindlimb adaptation of Megalancosaurus species are more similar to that of some small arboreal mammals rather than that of chameleons.
Keywords: Megalancosaurus (Diapsida Drepanosauromorpha); Triassic; functional morphology; interspecific variation; osteology; locomotion; palaeoecology.